Cardiac transplant recipient with COVID-19 induced acute hypoxic respiratory failure: a case report. Issue 6 (26th June 2021) - Schreiber, Ariyon; Elango, Kalaimani; Hong, Kimberly; Ahsan, Chowdhury
Abstract: Background: Heart transplant recipients represent a particularly vulnerable patient population to the novel coronavirus disease 2019 (COVID-19) due to chronic immunosuppression and high rates of comorbidities. Currently, data are limited and evidence to guide management of heart transplant recipients with COVID-19 is sparse. In this case report, we provide a summary of the current literature as well as an in-depth analysis of our clinical decision-making. Case summary: A 67-year-old female who underwent cardiac transplantation 1 year prior was found to have acute hypoxic respiratory failure due to COVID-19. Her immunosuppressant medications were modulated with discontinuation of mycophenolate and titration of tacrolimus troughs with a goal of 6–10 ng/dL. She was administered supportive treatment including convalescent plasma, remdesivir, and dexamethasone, in addition to antibiotic treatment that resulted in resolution of her symptoms within a matter of days despite her precarious disposition. Discussion: This case demonstrates that it can be safe and efficacious to modulate immunosuppressant medications in cardiac transplant recipients in accordance with recommendations made by the International Society of Heart and Lung Transplantation. This case additionally demonstrates that aspects of the current literature regarding the management of COVID-19 can be safely extrapolated to cardiac transplant recipients. Providing supportive care with dexamethasone, remdesivir, and convalescent plasma as indicated can be beneficial in cardiac transplant recipients; although, the current literature regarding convalescent plasma and remdesivir is conflicting.